Evaluation of Salivary Chemerin and Visfatin in Relation to Periodontitis and Obesity - Farah Razak Abood; Zainab A. Aldhaher (Ibn Al-Haitham Journal for Pure and Applied Sciences)
Periodontitis is a common disorder caused by imbalanced plaque biofilms and associated with gradual deterioration of the teeth supporting apparatus. Obesity is documented as a significant health concern and considered a primary risk factor for the progression of many diseases, such as hypertension, diabetes, malignancies, and periodontitis. Proinflammatory cytokines released in response to these health conditions are of great importance and establish the link between diagnosis and treatment. The present study was conducted to assess levels of chemerin and visfatin in saliva and to evaluate the impact of obesity on periodontitis. Ninety participants were included in the study and dived into three groups: (Group I: obese and periodontitis patients, n = 30), (Group II: periodontitis patients, n = 30) and (Group III: healthy controls, n = 30). We selected all participants based on their BMI measurement and examination of periodontal parameters. Unstimulated saliva was the obtained sample for evaluation of chemerin and visfatin using the ELISA technique. The study results found that chemerin and visfatin levels were different among study groups, but group I members have the highest levels, followed by group II and group III. In conclusion, obesity has a high impact on periodontitis through the expression of proinflammatory biomarkers in saliva like adipokines (cytokines produced by adipose tissue).